Toward innovative veterinary nanoparticle vaccines - Meiqi Sun; Aldryan Cristianto Pratama; He Qiu; Zehui Liu; Fang He (BMC, 2024)
Abstract Nanoparticles are significant for veterinary vaccine development because they are safer and more effective than conventional formulations. One promising area of research involves self-assembled protein nanoparticles (SAPNs), which have shown potential for enhancing antigen-presenting cell uptake, B-cell activation, and lymph node trafficking. Numerous nanovaccines have been utilized in veterinary medicine, including natural self-assembled protein nanoparticles, rationally designed self-assembled protein nanoparticles, animal virus-derived nanoparticles, bacteriophage-derived nanoparticles, and plant-derived nanoparticles, which will be discussed in this review. SAPN vaccines can produce robust cellular and humoral immune responses and have been shown to protect against various animal infectious diseases. This article attempts to summarize these diverse nanovaccine types and their recent research progress in the field of veterinary medicine. Furthermore, this paper highlights their disadvantages and methods for improving their immunogenicity.